To show that x + 4 is a factor of V(x), we can use the Remainder Theorem. If V(-4) = 0, then x + 4 is indeed a factor.
Evaluate V(-4):
V(-4) = (-4)^3 - 2(-4)^2 - 19(-4) + 20
V(-4) = -64 - 2(16) + 76 + 20
V(-4) = -64 - 32 + 76 + 20
V(-4) = 0
Since V(-4) equals 0, we can conclude that x + 4 is a factor of V(x).
Now, to factor V(x) completely, we can use synthetic division or polynomial long division to divide V(x) by (x + 4):
The result of the division is the quotient 1x^2 - 6x + 7 and a remainder of 8.
So, V(x) can be factored as:
V(x) = (x + 4)(x^2 - 6x + 7)
Now, let's further factor the quadratic expression x^2 - 6x + 7:
x^2 - 6x + 7 = (x - 1)(x - 7)
Now, we have factored V(x) completely:
V(x) = (x + 4)(x - 1)(x - 7)
So, the complete factorization of V(x) is
(x + 4)(x - 1)(x - 7).